Banten’s Karangantu Port as the Maritime Axis of Southeast Asia in the 16th -18th Century - Ahmad Fauzan Baihaqi; Bryna Rizkinta Sembiring Meilala; Fauzan Syahru Ramadhan; Ade Mahmud Supriatna (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2026)
This article aims to analyse the socio-economic dynamics and the role of the sultanate in developing Karangantu Port as an international trade centre in Java. During the 16th-18th centuries, Karangantu Port played a role in replacing Malacca as the centre of trade in Southeast Asia. This study employs historical methods, including the heuristic, verification, interpretation, and historiography stages, supported by a socio-economic historical approach. The results of the study show that the strategic location of Karangantu Port and its well-organised infrastructure attracted foreign traders, making it a cosmopolitan trading centre. The rapid growth of trading activities at this port was supported by sultanate policies, such as free trade, infrastructure development, and diplomatic relations with other kingdoms. The livelihoods of the people of Banten, including farmers, fishermen, craftsmen, and traders, contributed to the port's economic growth. Sultan Ageng Tirtayasa's efforts to expand Banten's influence and prevent Dutch monopoly, although ultimately unsuccessful due to internal conflicts, demonstrate the port's importance in the regional maritime trade network. Banten's rise as an economic centre, facilitated by the growth of Karangantu Port, benefited the pepper trade as a major commodity, attracting foreign merchants. The development of this port was also influenced by the fall of Malacca to the Portuguese in 1511, which diverted the spice trade route through the Sunda Strait. The role of Karangantu Port as an international transit port allowed traders from various countries and cultures to participate in trading activities, shaping the socio-economic landscape of the Sultanate of Banten from the 16th to 18th centuries AD.